Experimental study on the influence of acid fracturing fluid on coal wettability. (1st July 2023) - Zhang, Yi; Zheng, Yuannan; Jiang, Bingyou; Yu, Guofeng; Ren, Bo; Yu, Changfei; Wang, Shiju
Highlights: Electrostatic repulsion reduction between ions in CTAB caused by HCl. HCl has a great influence on CTAB, and the surface tension is reduced by 10 ∼ 30 mN/m. Coal surface roughness becomes smaller after treated with acid fracturing fluid. HCl and CTAB have synergistic effect on the improvement of coal wettability. Abstract: With the continuous improvement of mechanized mining intensity, dust has seriously threatened the safety of mine production and the health of underground workers. Coal seam water injection is one of the effective means to moisten the primary coal dust in the coal body. Through testing by the surface tension tester, contact angle meter, FTIR, low-temperature liquid nitrogen adsorption, and SEM, the impact of acid fracturing fluid which can be used for coal seam water injection on the wettability and pore structure of coal was studyed. The results showed that HCl and CTAB had good synergistic acidification effect, which can effectively reduce the surface tension of CTAB by 10 ∼ 30 mN/m. Also the contact angle between the solution and the coal sample is significantly affected by the acidity of the solution. However, the impact of the acid fracturing fluid varies for coal with differing levels of metamorphism and mineral content. For low rank bituminous coal, the contact angle decreased by 39.55° after contact with the sample surface for 1 s, and the solution was completely immersed in the coal body after 5 s. The absorbance of hydrophilic functional groups of coal becomes stronger after treatment with acid fracturing fluid, which is conducive to upgrading the wettability of coal. Meanwhile, the acid fracturing fluid increases coal's connectivity and average pore diameter, which in turn influences the wettability of coal. Exploring the influence of acid-based fracturing fluid on coal can provide guidance for improving the wettability of coal, reducing dust concentration and optimizing the underground working environment.